Development of a virtual reality clinically oriented temporal bone anatomy module with randomised control study of three-dimensional display technology. (14th December 2020) - Copson, Bridget; Wijewickrema, Sudanthi; Sorace, Laurence; Jones, Randall; O'Leary, Stephen
Abstract : Objective: To investigate the effectiveness of a virtual reality (VR), three-dimensional (3D) clinically orientated temporal bone anatomy module, including an assessment of different display technologies. Methods: A clinically orientated, procedural and interactive anatomy module was generated from a micro-CT of a cadaveric temporal bone. The module was given in three different display technologies; 2D, 3D with monoscopic vision, and 3D with stereoscopic vision. A randomised control trial assessed the knowledge acquisition and attitudes of 47 medical students though a pretutorial and post-tutorial questionnaire. The questionnaire included questions identifying anatomic structures as well as understanding structural relations and clinical relevance. Furthermore, a five-point Likert scale assessed the students' attitudes to the module and alternative learning outcomes, such as interest in otology and preparedness for clinical rotations. Results: As a whole cohort, the total test score improved significantly, with a large effect size (p≤0.005, Cohen's d=1.41). The 23 students who returned the retention questionnaire had a significant improvement in total test score compared with their pretutorial score, with a large effect size (p≤0.005, Cohen's d=0.83). Display technology did not influence the majority of learning outcomes, with the exception of 3D technologies, showing a significantly improvement in understanding of clinical relevance and structural relations (p=0.034). Students preferred 3D technologies for ease of use, perceived effectiveness and willingness to use again. Conclusions: The developed VR temporal bone anatomy tutor was an effective self-directed education tool. 3D technology remains valuable in facilitating spatial learning and superior user satisfaction.